STRUKTUR HUKUM ISLAM “STUDI PEMIKIRAN FAZLUR RAHMAN” - Mirwan (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2020)
The legal aspect in Islam is closely related to the process of itsdetermination (istinbat al-ahkam) according to jurisprudents. In themethod of extracting Islamic law, the jurists, hierarchically, refer to alQur‘an, as-Sunnah, Ijma` (consensus) and Qiyas (analogy). However, theabove hierarchy is not fully used sequentially. In other words the jurorsare not in the same opinion how the application of the existing methods.Like the practice adopted by one of the contemporary Islamic thinkersFazlul Rahman.According to Fazlur Rahman, in interpreting the qur`an, it is appropriateto use a method called